A distributed solar collector field temperature profile control and estimation using inlet oil temperature and radiation estimates based on Iterative Extended Kalman Filter. (February 2017) - Karamali, Mohammad; Khodabandeh, Mahdi
Abstract: In this article, two different state space models for a distributed solar collector field have been extracted. Design of an Iterative Extended Kalman Filter (IEKF) and an appropriate controller for the distributed solar collector field and their simulations are the other purposes of this study. A feed forward controller, moreover the PID controller, has been used in the designed controller the in order to attenuate the disturbances effects caused by solar radiation, inlet oil temperature and environmental temperature. Both of the models can be used to estimate the distributed solar collector field temperature profile. It has been shown that the temperature of all parts of the solar collector field such as inlet oil temperature can be estimated by using the models in Iterative Extended Kalman Filter (IEKF) only by use of one sensor to measure the temperature along the collectors. Also it has been exposed that the used Kalman Filter could greatly eliminate the applied noises to the system, and thus makes the system robust against the influencing noises such as sensors errors. All required parameters for implementation of the Iterative Extended Kalman Filter and the controller and simulation has been extracted from Shiraz solar power plant. Highlights: A Control and estimation structure for temperature profile of Shiraz solar power plant has been introduced. Feed forward and PID controllers have been designed to attenuate the disturbances effects. The considered disturbances are solar radiation, inlet oil temperature and environmental temperature. An Iterative Extended Kalman Filter (IEKF) to eliminate the applied noises for the system has been designed. Temperature of all parts of the solar collector field has been estimated by IEKF only by use of one sensor measurement.